Yttrium trihydride enhanced lithium storage in carbon materials. (30th August 2020) - Zheng, Xinyao; Li, Guoling; Guo, Yanru; Yu, Hongen; Li, Shuan; Xiao, Rui; Zheng, Jie; Li, Xingguo
Abstract: Metal hydrides (MHx ) are gaining increasingly interest as anode materials for lithium ion batteries. The most widely accepted lithium storage mechanism for MHx is the conversion mechanism to form LiH. Our previous study suggested a different lithium storage mechanism of rare earth trihydride (REH3, RE = Y, La and Gd)-graphite composite: the reactive H released from the REH3 -REH2 conversion may enhance the lithium storage capacity of graphite by forming a Li–C–H composite. In this work, this interesting phenomenon is further studied by comparing the lithium storage performance of YH3 /carbon composite using different carbon materials: graphite, acetylene black, activated carbon and commercial graphene. The enhanced lithium storage capacity by YH3 addition is only observed for graphite, indicating the essential role of the intact layered graphene structure in this new lithium storage mechanism. Graphical abstract: Image 1 Highlights: The reactive H released from REH3 -REH2 conversion enhances lithium storage capacity of graphite. The lithiation product of YH3 /graphite is Li–C–H composite instead of LiCx . YH3 can only enhance graphite due to the essential role of the intact layered graphene structure.